Development of CHEMISTER as Chemistry Education Media with Socioscientific Issues Approach Integrated with Augmented Reality to Support Education for Sustainable Development - Deaningtyas, Sukma Ayu; Purwandari, Afifa; Sentanu, Naufal Albion Zhafran; Rafsanjani, Esa Refrisa; Kamaliyah, Nur Laila; Setiawan, Nur Candra Eka (Universitas Negeri Malang, 2024)
Learning in Indonesia currently still focuses on theoretical knowledge, so that the implementation of Education for Sustainable Development (ESD) is not optimal. Chemistry is a suitable subject to teach sustainable principles in accordance with ESD principles, especially on the topic of reaction rate. However, there are problems for students in understanding the reaction rate, as evidenced by students' concept understanding of this material being only 26%, and only 33.3% of students managed to get a score above the KKM. These problems can be caused by the limited learning media that facilitate students in learning the reaction rate. Therefore, this research aims to develop educational kit-based learning media on reaction rate material with the Socioscientific Issues (SSI) approach integrated with augmented reality technology as an effort to support ESD. This research method uses Research and Development (RnD) level 1 with five stages, namely potential and problems, literature study and information gathering, product design, design validation, and tested design. The results showed that the learning media presented in the form of educational kits with the SSI approach equipped with mobile applications, game cards, flashcards, and practicum kits with the concept of green chemistry have been produced. This product is a suitable educational media in an effort to improve the quality of education through the implementation of ESD.